Methylmercury uptake and bioconcentration by the freshwater green alga Pseudokirchineriella subcapitata - Nwobu, Ogochukwu L (University of Ottawa (Canada), 2005)
Methylmercury (MeHg) enters most aquatic food webs primarily at the phytoplankton level. However, in the complex aquatic ecosystem, it is difficult to fully examine specific pathways. Consequently, in this study, the uptake of environmentally realistic levels of added MeHg concentrations (0.21 to 20 ng Hg L-1 ) by the freshwater green alga Pseudokirchniriella subcapitata grown in batch and semi-continuous cultures at biomass levels of (0.03, 0.15, 0.3 and 3 mg (dw) L-1) was investigated. In algal culture media without dissolved organic carbon (DOC) and in river water samples with DOC concentration of (2.8 mg L-1) uptake, uptake rate constant, algal concentration of MeHg and the bioconcentration factor (BCF) after 48 h was measured. MeHg uptake was biphasic, with rapid uptake of at least 50% of the total uptake taking place over the first 2 h of incubation followed by a more gradual uptake for the remaining 46 h. Desorption of MeHg from algal cells by re-suspension in acidic medium (pH 3) was < 10% of the total uptake at 48 h. Uptake rate constants of MeHg (ku) increased with aqueous MeHg concentration (r2 = 0.99). At 48 h, algal concentration of MeHg (MeHg (ng) divided by dry weight of algal biomass (g)) increased with aqueous MeHg concentration (r2 = 0.98) but decreased with increasing biomass (r2 = 0.75). This was shown to be a biomass dilution effect as the total uptake of MeHg did increase with biomass. Log MeHg BCF decreased with increasing algal biomass (r 2 = 0.99) with values of 6.9, 6.2 and 5.2 at 0.03, 0.3 and 3 mg (dw) L-1 respectively at all concentrations of MeHg added (0.5, 1.0 and 20 ng L-1).
Keywords: Biology, Ecology.; Environmental Sciences.; Agriculture, Fisheries and Aquaculture.